New International Calibration Standard (ICS-R2) for HPLC Analysis of Reduced (rho) iso-α-acids: Submitted on behalf of the International Subcommittee for Isomerized Hop-Acids - Wilson, Richard (BrewingScience, 2005)
The International Subcommittee for Isomerized Hop α-Acids Standards (ISIHAS), announces the release of a new calibration standard, ICS-R2, for the HPLC analysis of reduced (rho) iso-αacids. This standard replaces ICS-R1, which is now withdrawn.